Uji Efektivitas Waktu Pemberian Nutrisi Terhadap Produksi Selada Hijau (Lactuca sativa L) Varietas New Grand Rapids Pada Sistem Aeroponik - Rommy Andhika Laksono; Netti Nurlenawati (Paspalum: Jurnal Ilmiah Pertanian, 2021)
The demand for lettuce in Indonesia still cannot be fulfilled because lettuce production in Indonesia is still very low according to data from the Indonesian Central Statistics Agency in 2019. To meet the needs of lettuce at the request of the community and the market, an intensive cultivation technique is needed, namely the aeroponic system. The purpose of this study was to get the right timing of nutrition to produce the highest production of green lettuce plants in an aeroponic system. The research method used is an experimental method with the environmental design used is a Single Factor Randomized Block Design (RBD), which consists of 6 treatments repeated 4 times. The treatments consisted of t1 (5 minutes off, 30 seconds on), t2 (10 minutes off, 30 seconds on), t3 (15 minutes off, 30 seconds on), t4 (20 minutes off, 30 seconds on), t5 (25 minutes off, 30 seconds on), t6 (non-stop). Analysis of the data used is the F test at 5% level and to find out which treatment is the best, DMRT further test is carried out at the 5% level. The results showed that the t6 treatment gave better growth and yields than other treatments. At the age of 42 days after observation, the average plant height was 29.4 cm; the average number of leaves 15.22; the average diameter of the rods is 14.11 mm; mean root length 10.34 cm; 2003 mean leaf area, 59 cm2 ; and the average fresh weight was 670.1 g.